Physical Grinding of Prefabricated Co3O4 and MCM-22 Zeolite for Fischer–Tropsch Synthesis: Impact of Pretreatment Procedure on the Dispersion and Catalytic Performance - Hua-Ping Ren; Zhi-Xia Xie; Shao-Peng Tian; Si-Yi Ding; Qiang Ma; Yu-Zhen Zhao; Zhe Zhang; Jiao-Jiao Fu; Qing-Qing Hao (Molecules, 2024)
To improve the mess-specific activity of Co supported on zeolite catalysts in Fischer–Tropsch (FT) synthesis, the Co-MCM-22 catalyst was prepared by simply grinding the MCM-22 with nanosized Co3O4 prefabricated by the thermal decomposition of the Co(II)-glycine complex. It is found that this novel strategy is effective for improving the mess-specific activity of Co catalysts in FT synthesis compared to the impregnation method. Moreover, the ion exchange and calcination sequence of MCM-22 has a significant influence on the dispersion, particle size distribution, and reduction degree of Co. The Co-MCM-22 prepared by the physical grinding of prefabricated Co3O4 and H+-type MCM-22 without a further calcination process exhibits a moderate interaction between Co3O4 and MCM-22, which results in the higher reduction degree, higher dispersion, and higher mess-specific activity of Co. Thus, the newly developed method is more controllable and promising for the synthesis of metal-supported catalysts.